Some Pharmacological Tests of Datisca cannabina Linn: Pharmacological Screening of Datisca cannabina Linn - Zainab; Aziz , Abdul; Shah, Muddaser; Muhammad, Noor; Mehjabeen; Jahan, Noor; Ur Rehman, Najeeb; Al-Harrasi, Ahmed; Ahmad, Manzoor (Iranian Journal of Pharmaceutical Sciences, 2025)
In the current study, methanolic extracts (DCME) along with their fractions (n-hexane (DCHF), chloroform (DCBF), ethyl acetate (DCEF), n-butanol (DCBF), and aqueous (DCAF) of Datisca Cannabina Linn. were examined for in vitro biological activities, i.e., phytotoxicity, cytotoxicity, antioxidant, hemagglutination bioassay, urease, and spasmogenic and spasmolytic activities. Our findings revealed that the study plant is non-toxic, as neither its crude extract nor its subfractions exhibited toxic effects against brine shrimp. Additionally, no significant insecticidal activity was observed in the crude extracts or subfractions. Furthermore, the crude extract showed significant analgesic potential compared to the other tested samples, indicating the presence of bioactive constituents in the crude methanol extract. In the case of hemagglutination activity, all extracts exhibited a high (+++) or medium (++) agglutination effect against all human blood groups at a 5 mg/mL concentration, except for blood groups B and A, where the effect was low. Similarly, the crude methanol and aqueous fractions were found to have maximum (90%) and minimum (80%) phytotoxic activity, respectively, at a higher concentration (1000 μg/mL) only. In the case of urease enzyme inhibition studies, the ethyl acetate fraction showed maximum inhibition (90%), followed by DCBF (88%) and DCAF (70%), while the other fractions were found to be inactive. Among all the fractions screened, the same fraction (DCEF, 86.0%) displayed the highest antioxidant activity, followed by the chloroform fraction (75%) compared to standard BHA (92.25%) at a concentration of 1.0 mg/ml. In terms of spasmogenic and spasmolytic significance, D. cannabina’s fractions were found to have a mild contracting and relaxing effect, varying from low to high doses, which may explain the traditional use of the plant in treating constipation and abdominal cramps, respectively.